#### Answer

f(-1)=8

#### Work Step by Step

f(x)=$x^{3}$-2x+7
f(-1)=$(-1)^{3}$-2(-1)+7
f(-1)=-1+2+7
f(-1)=8

Published by
Pearson

ISBN 10:
0321726391

ISBN 13:
978-0-32172-639-1

f(-1)=8

f(x)=$x^{3}$-2x+7
f(-1)=$(-1)^{3}$-2(-1)+7
f(-1)=-1+2+7
f(-1)=8

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.